A novel approach to activate deep spinal muscles in space—Results of a biomechanical model. (November 2015) - Lindenroth, Lukas; Caplan, Nick; Debuse, Dorothée; Salomoni, Sauro Emerick; Evetts, Simon; Weber, Tobias
Abstract: Introduction: Exposure to microgravity has various effects on the human musculoskeletal system. During spaceflight many astronauts experience low back pain and the risk of spine injuries is significantly greater post-flight. Nonetheless, the increased lumbo-pelvic injury risk is not specifically addressed by current countermeasures. Considering this, a novel exercise device has been developed to specifically counteract atrophy of deep spinal and postural muscles. The aim of the present study was to test the possibility of transferring this exercise concept from earth to space using a biomechanical simulation. Methods: A biomechanical model of the exercise device was developed and validated using intramuscular electromyographic (EMG) data as previously acquired on a terrestrial prototype of the exercise device. The model was then modified to the needs of a 0- g environment, creating gravity-like conditions using shoulder straps. Results: Modelled activation patterns of the investigated muscles were in line with the experimental data, showing a constant activation during exercise. The microgravity modifications of the model lead to increased muscle activation of deep spinal muscles and to decreased activation of superficial moment creating trunk muscles. Discussion: The results of the biomechanical model suggest that the exercise concept can be transferred from 1- g to space conditions. The present study is a first step in the investigation process of a novel exercise concept and human studies should be conducted to confirm the present theoretical investigation. Highlights: Biomechanical modelling of novel exercise device. Shown to activate postural stabilizing muscles. Model validation through intramuscular electromyographic data. Simulation shows promising activation of relevant muscle groups. Model adaptations reveal possible use as countermeasure for astronauts in 0 g .